MODEL PEMBEBANAN LALU LINTAS UNTUK TIPIKAL JARINGAN JALAN PERKANTORAN - Natalia Tanan (Direktorat Bina Teknik Jalan dan Jembatan, 2009)
Indonesia cities always face transportation problem. The movement in the urban road network needs transportation means, services and infrastructures. Therefore, trip assignment pattrn of urban road network needs to be researched. There are several Trip Assignment Methods which can be used to calculate the traffic volume on each modeled roads. In this paper, two methods of traffic assignments are used, i.e.. All or Nothing and Equilibrium. To find the best method, the predicted traffic flow produced by each model was compared to the real traffic flow collected by traffic counting survey. Traffic flow from 11 links were taken for comparison. These cover the movements on arterial, collector, and local roads. The result showed that equilibrium method gave the best result for the rural network at Kota Cimahi (such as Jl.Ciwaruga-Jl Cibabat, Jl Kol. Masturi-Lembang, Jl. Soreang-Nanjung). Keywords: traffic flow, road network, assignment all or-nothing, equilibrium